2022
DOI: 10.1111/2041-210x.13789
|View full text |Cite
|
Sign up to set email alerts
|

BoomBox: An Automated Behavioural Response (ABR) camera trap module for wildlife playback experiments

Abstract: Camera traps (CTs) are a valuable tool in ecological research, amassing large quantities of information on the behaviour of diverse wildlife communities. CTs are predominantly used as passive data loggers to gather observational data for correlational analyses. Integrating CTs into experimental studies, however, can enable rigorous testing of key hypotheses in animal behaviour and conservation biology that are otherwise difficult or impossible to evaluate. We developed the 'BoomBox', an open‐source Arduino‐com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…To understand the fear response of ungulates to elephants, we used ABRs to play recordings of three vocalizations: elephants, leopards and procedural controls [ 20 , 22 , 26 ]. The leopard is the primary apex predator in our study area and has previously been shown to induce the greatest fear responses from ungulates in this area [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the fear response of ungulates to elephants, we used ABRs to play recordings of three vocalizations: elephants, leopards and procedural controls [ 20 , 22 , 26 ]. The leopard is the primary apex predator in our study area and has previously been shown to induce the greatest fear responses from ungulates in this area [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…To determine if megaherbivores can induce fear in other mammals, we contrasted the behavioural responses of medium- to large-sized ungulates to cues of a megaherbivore, the African bush elephant ( Loxodonta africana ), relative to a common predator, the leopard ( Panthera pardus ), in an African savannah. To isolate behavioural responses, we used an automated behavioural response (ABR) system comprised of a motion-activated camera and speaker [ 20 ]. This ABR system allowed quantification of reactive responses (as opposed to proactive responses [ 21 ]) of ungulates to different cues.…”
Section: Introductionmentioning
confidence: 99%
“…Some automatic devices already exist to make some playback experiments as BoomBox: an automated behavioral response (ABR) camera trap module for wildlife experiments (Palmer et al, 2022). Food containers of various kinds have been used in field experiments (De la Fuente et al, 2022; Van de Waal et al, 2013), and robots are increasingly used with wild animals (Grémillet et al, 2012; Le Maho et al, 2014).…”
Section: Future Research Frameworkmentioning
confidence: 99%
“…[2e.g. [22] , [23] , [24] ). The broadcast by motor sensor limits functionality to test certain questions related to the social information hypothesis, such as habitat selection (for breeding, winter, or stopover habitats), mating choices, and/or triggering fright responses.…”
Section: Hardware In Contextmentioning
confidence: 99%